2019
DOI: 10.1016/j.dynatmoce.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Amazon River plume influence on Western Tropical Atlantic dynamic variability

Abstract: This study focuses on analysing the potential impact of the Amazon and Pará Rivers on the salinity, temperature and hydrodynamics of the Western Tropical North Atlantic (WTNA) region between 60.5°-24 °W and 5 °S-16 °N.The Regional Ocean Model System (ROMS) was used to simulate ocean circulation with 0.25° horizontal resolution and 32 vertical levels. Two numerical experiments were performed considering river discharge and river input. Temperature and salinity distributions obtained numerically were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 68 publications
(90 reference statements)
0
43
0
1
Order By: Relevance
“…However, there are a few quantitative descriptions of the flocculation effect on sediment dispersion and deposition [2,4]. Meanwhile, dynamic behaviors of the whole river plumes, including buoyant jets or bulges of small scale, have been explored by field observations, satellite image analysis, and numerical simulations, for example, for Mackenzie River plumes [5], Yellow River sediment plumes [6,7], Pearl River plumes [8], Columbia River plumes [9], small-mouth Kelvin number plumes [10], and Amazon River plumes [11,12]. With respect to the ecosystem in coastal regions, there are some remote-sensing studies of river sediment plume dynamics from the spatio-temporal variations of suspended sediment concentration (SSC; mg/L) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few quantitative descriptions of the flocculation effect on sediment dispersion and deposition [2,4]. Meanwhile, dynamic behaviors of the whole river plumes, including buoyant jets or bulges of small scale, have been explored by field observations, satellite image analysis, and numerical simulations, for example, for Mackenzie River plumes [5], Yellow River sediment plumes [6,7], Pearl River plumes [8], Columbia River plumes [9], small-mouth Kelvin number plumes [10], and Amazon River plumes [11,12]. With respect to the ecosystem in coastal regions, there are some remote-sensing studies of river sediment plume dynamics from the spatio-temporal variations of suspended sediment concentration (SSC; mg/L) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The regional circulation in the western tropical Atlantic is dominated by the NBC, an intense western boundary current. The maximum Amazon discharge during May‐June (Fournier et al., 2017; Masson & Delecluse, 2001; Silva et al., 2005; Varona et al., 2019), and Orinoco discharge during July‐August (Fournier et al., 2017) causes a surface plume of freshwater which spreads northwestward due to the NBC and associated rings, not just during the months of maximum river discharge, but all year round. Previous studies have shed some light on the advection of the Amazon/Orinoco freshwater and their interaction with the seasonally varying NBC and NBC rings (Ffield, 2007; Fournier et al., 2017; Fratantoni & Glickson, 2002).…”
Section: Barrier Layer Growth and Decay In The Nbc Rings Areamentioning
confidence: 99%
“…The sea surface temperatures are strongly influenced by rainfall changes in the Amazon River basin, impacting the river discharge and consequently the sea surface salinity in the Amazon plume (Hu et al, 2004;Vizy & Cook, 2010). Low-salinity surface waters are found as far as 2000 km at an average depth of 20-30m from the mouth (Gouveia et al, 2019;Tyaquiçã et al, 2017;Varona et al, 2019). It is one of the greatest discharges of fresh water and suspended sediments in the world, previously presented as a barrier for the dispersal of other organisms such as bacterioplankton, coral and lionfish (de Souza et al, 2017;Hewson et al, 2006;Luiz et al, 2013).…”
Section: Species Delimitation Of Recent Divergent Populations Within mentioning
confidence: 99%
“…A number of mechanisms have been proposed to account for this astonishing biodiversity and current distributions of many groups of marine organisms. Habitat choice by settling larvae has been shown to be responsible for maintaining a mosaic genetic structure in two mussel species in a small geographic scale (Barrett, 2017;Bierne et al, 2003;Frolova & Miglietta, 2020); adaptation to alternative water temperatures maintains reproductive isolation between sister species of Halichoeres fishes (Rocha et al, 2005); reduced gene flow between continental and oceanic islands coasts has been shown to drive divergence in shallow-water reef-associated species (Hachich et al, 2015); sister lineages of Antarctic krill species have been shown to have diverged due to the formation of circum-Antarctic water circulation and the Antarctic Polar Frontal Zone (Patarnello et al, 1996); major dispersal barriers such as the Amazonian Orinoco Plume and the Mid-Atlantic Barrier, the Isthmus of Panama, among others, are also known to promote divergence as the result of vicariance or long distance dispersal across them, followed by local adaptation (Cowman & Bellwood, 2013;Luiz et al, 2013;Varona et al, 2019). Regardless of the spatial configuration in which the divergence takes place (i.e.…”
Section: Introductionmentioning
confidence: 99%